Enhancing the performance of common electrode materials by means of atmospheric plasma spray coatings. (February 2016) - Robotti, M.; Dosta, S.; Gardon, M.; Cano, I.G.; Guilemany, J.M.; Kourasi, M.; Mellor, B.; Wills, R.
Highlights: CTE mismatch can be effectively controlled for Al and stainless steel thin sheets. Fragile carbon–polymer composites and delicate Ni foams were properly coated. The same low energetic spraying conditions successfully coated all four electrode materials. Abstract: Atmospheric plasma spraying is used here to obtain titanium sub-oxide coatings on the following electrode substrates: a 316 stainless steel sheet, an aluminium alloy 2024 sheet, a carbon–polymer composite and nickel foam. It is necessary to increase the roughness of the substrate to aid the adhesion of the coating to the smooth electrodes; this is especially critical for the fragile carbon–polymer composite. High-energy conditions increase the strain caused by the mismatch between coefficients of thermal expansion when coating the thin steel and aluminium sheets, and degraded the carbon–polymer composite and nickel foam. Therefore, it is necessary to adjust the spraying parameters to lower-energy conditions in order to achieve well-bonded and homogeneous coatings on all four substrates and avoid the presence of cracks in their cross-section area. The suitability of the coated materials as battery electrodes was studied.